PROBLEMATIKA PRODUK HUKUM CAMAT SEBAGAI PEJABAT PEMBUAT AKTA TANAH SEMENTARA (PPAT/S) DALAM MELAKSANAKAN PERALIHAN HAK ATAS TANAH TANPASERTIFIKAT - KHAIRUNISYAH HARAHAP (PREMISE LAW JURNAL, 2014)
ABSTRACT Article 37, paragraph 1 of PP (Government Regulation) No. 24/1997 on Land Registration states that “Endorsement on land and ownership of a unit of high-rise through buying-selling, exchanging, granting, income for a company, and legal action for the endorsement, except the endorsement is caused by auction, can be registered if only it can be proved by a deed written by a PPAT (official empowered to draw up land deeds) who has the authority, according to the prevailing regulations.” In practice, however, a Subdistrict head as an interim PPAT does the endorsement on land without any certificate. The result of the research showed that, A Subdistrict head as an interim PPAT signs a PPAT certificate on land right in the form of buying and selling without any certificate in AJB form to be filled in since the land has not been registered. Therefore, it is recommended that people should register the lands first before a PPAT or a Subdistrict head as an interim PPAT before the endorsement of the land is done so that the PPAT certificate becomes an authentic data as it is stipulated in Article 1868 of the Civil Code. Keywords: Problems, Subdistrict Head as an Interim PPAT, Endorsement on Land Right, Non-Certificate